Pemanfaatan Sistem Otomatisasi Kantor dalam Menunjang Efektivitas Kinerja Karyawan Pada PT Kereta Api Indonesia Persero - Abi Sopyan Febrianto; Putri Nurwaqiah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
In achieving the goals, companies need human resources who have skills, are broad-minded, and support the vision carried by the company. In addition, the company's success is also influenced by technology to achieve increased employee performance in carrying out business operations. This study aims to determine the impact of using office automation systems in supporting the effectiveness of employee performance at PT Kereta Api Indonesia, General Document Secretary Unit. This research is a descriptive qualitative research. Methods of data collection through interviews for primary data and credible electronic sources with research topics for secondary data. Data is presented in the form of descriptive analysis. The results of the study illustrate that the use of office automation systems at PT Kereta Api Indonesia, the General Document Secretary Unit has an impact on the effectiveness of employee performance. The results of this study contribute to enriching the academic literature on office automation systems and employee performance.